Strategies for Community Empowerment in Utilizing the Economic and Ecological Functions of Sustainable Mangrove Ecosystems in Jeneponto District, South Sulawesi - Handayani, Fitri; Arfan, Amal; Sideng, Uca (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2024)
Mangrove forests in Balang Baru Village, Tarowang District have great potential for sustainable utilization of the economic and ecological functions of the mangrove ecosystem. Various potentials of the mangrove ecosystem in Balang Baru Village, Tarowang District include providing ecosystem services in the form of fish and other biota and multiple types of species that have economic value. Another potential of the mangrove ecosystem in Balang Baru Village, Tarowang District is its utilization as a nature-based tourism area. These various potentials can contribute to the welfare of local communities if they are utilized and managed sustainably. This study aims to analyze the potential area of mangrove forests, economic and ecological function services of mangrove ecosystems, perceptions and levels of community participation in mangrove ecosystem services, and create community empowerment strategies in utilizing of economic and ecological functions of mangrove forests. Data analysis of mangrove forest potential area by interpreting of LandSat 8 Satellite Imagery. Mangrove ecosystem benefits are calculated through economic valuation. Perception and level of community participation using Likert scale and tabulated in a frequency table. Data from in-depth interviews, FGDs, mangrove forest potential, perceptions, and levels of community participation were analyzed using SWOT. Determination of community empowerment strategies in utilizing the economic and ecological functions of the mangrove ecosystem is carried out by determining internal and external factors, compiling a SWOT matrix, then calculating the IFAS and EFAS matrices, and determining the location of the SWOT quadrant. The area of mangrove forest in Jeneponto Regency is 158.14 hectares. The total economic value of mangrove forests is Rp. 17,970,053,940/year or Rp. 1,046,596,036.113/ha/year. Community perceptions of mangrove ecosystem functions are influenced by the level of knowledge and education of the community. Local communities are involved in the utilization and management of mangroves. Priority strategies are developing the potential of sustainable and economically valuable mangrove forest resources, improving information, facilities and infrastructure that can support community empowerment activities, increasing promotion of ecotourism through online media, implementing conservation area policies and utilizing mangrove ecosystems, and increasing planting activities by involving various parties.